2017
DOI: 10.1186/s12883-016-0786-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetyl-DL-leucine on cerebellar ataxia (ALCAT trial): study protocol for a multicenter, multinational, randomized, double-blind, placebo-controlled, crossover phase III trial

Abstract: BackgroundCerebellar ataxia (CA) is a frequent and often disabling condition that impairs motor functioning and impacts on quality of life (QoL). No medication has yet been proven effective for the symptomatic or even causative treatment of hereditary or non-hereditary, non-acquired CA. So far, the only treatment recommendation is physiotherapy. Therefore, new therapeutic options are needed. Based on three observational studies, the primary objective of the acetyl-DL-leucine on ataxia (ALCAT) trial is to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…A significant improvement of SARA score and quality of life was also noted on 12 patients with Niemann-Pick disease class C after 1 month of acetylleucine administration [28]. A randomised and placebocontrolled clinical trial testing acetylleucine in cerebellar syndrome (ALCAT) is currently underway and could provide more evidence [29,30].…”
Section: Discussionmentioning
confidence: 94%
“…A significant improvement of SARA score and quality of life was also noted on 12 patients with Niemann-Pick disease class C after 1 month of acetylleucine administration [28]. A randomised and placebocontrolled clinical trial testing acetylleucine in cerebellar syndrome (ALCAT) is currently underway and could provide more evidence [29,30].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, N-acetyl-leucine has experienced a renaissance with renewed interest from both academia and industry as a promising treatment for several disorders with unmet medical needs including cerebellar ataxia [3,[6][7][8], cognition and mobility in the elderly [9], lysosomal storage disorders [10,11] migraine [12] and restless legs syndrome [13]. Given the broad therapeutic potential of N-acetyl-leucine, its pharmacodynamics and pharmacokinetics warrant further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to reduce postural imbalance caused by the vestibular lesion following unilateral labyrinthectomy in rats 12 . In vitro electrophysiological studies indicated that such a beneficial role of NAL might be mediated through restoration of previously abnormal membrane potential to a normal state, as demonstrated in vestibular nuclei in guinea pig 8,11 . Promising outcome following NAL treatment in improving ataxic symptoms were also observed among Niemann Pick disease patients, a neurodegenerative lysosomal storage disorder caused by mutation in cholesterol transporting NPC 1 and 2 genes 13,14 .…”
Section: Introductionmentioning
confidence: 90%
“…Recently, N-acetyl-leucine (NAL), an acetylated derivative of leucine has been shown to improve neurological functions in cerebellar ataxia 8,9 . The racemic mixture, N-acetyl-DL-leucine (ADLL) has been used as a medication for the treatment of acute vertigo and vertiginous symptoms in France since 1957; it is orally available and has an excellent safety profile 10 .…”
Section: Introductionmentioning
confidence: 99%